Assessment of Outcome in Hypospadias Surgery – A Review - Springer, Alexander (Frontiers in Pediatrics, 2014)
Hypospadias is a challenging field of urogenital reconstructive surgery with different techniques being currently used. Modern surgery claims that it is possible to create a functionally and cosmetically normal penis. Continuous re-evaluation and assessment of outcome may have a major impact on future clinical practice. Assessment of outcome includes: complication rate, cosmetic appearance of the penis, functional outcome (micturition, sexuality), and psychological factors such as quality of life and psychosexual life. This article briefly reviews current strategies of outcome assessment. Somehow in the future, we will be able to give an accurate estimation of the long-term consequences of being born with hypospadias.